E-Waste Management: Developing a Model for Effective Take Back System in India - Dr. Rajeev Srivastava (Srusti Management Review, 2015)
The electronics industry is the world’s largest and fastest growing industry. Last decade has seen tremendous growth in the field of information technology all over the world, especially in developing countries like India. This growth has brought a new kind of waste known as electronic waste or e-waste that is very harmful for human health and environment. Since this waste has very complex characteristics and requires an equally complex set of efficient technology and processes to deal with it. This study strives to develop a valid and reliable model for effective ewaste management in Indian context. Total 495 respondents participate in the survey. A multiple regression analysis was employed and the, ‘Collection and Recycling’ appeared as the best predictor, followed by ‘Rules and Regulation’, ‘Awareness’, ‘Responsibility’ and ‘Initiatives’. The e-waste management model developed in this research may be utilized for effective e-waste management in an organization.